Munchausen syndrome by proxy – a case report - Aleksandra Paturej; Milena Pogonowska; Bolesław Kalicki (Pediatria i Medycyna Rodzinna, 2019)
Child abuse may take different forms. Munchausen syndrome by proxy is a factitious disorder in which disease symptoms are induced in a dependent person so that the perpetrator could play the role of a caregiver. Parent (mother in most cases) is usually the perpetrator, and a child is usually the victim. The desire to draw the attention of medical personnel, which can be a psychological reward, is the main motivation for a person affected by Munchausen syndrome by proxy. The scale of the problem remains unknown due to diagnostic difficulties. We present a case of a 10-year-old girl who was initially hospitalised for more than 2 months due to unexplained bleeding from the lower gastrointestinal tract, and was then admitted to another paediatric unit due to consciousness disorders. Accurate diagnosis and prevention of further child maltreatment was possible due to collecting thorough medical history, diagnostic vigilance and cooperation between medical centres where the girl was hospitalised.